Problem-Based Learning and Think Pair Share in Improving Learning Result - Maulidha, Irma Ayu (Unversitas Negeri Malang, 2018)
The purpose of this research intended to manage the classes properly and be able to increase the students’ learning results by applying a combination of Problem-Based Learning and Think Pair Share. The method of this study used classroom action research. The subjects of this research are 12th grade students of the economic class in a senior high school in Malang. This study was conducted in two cycles. In each cycle held three meetings and at the end of the cycle conducted post-test that aims to measure the results of students. After the data received, then it was analyzed qualitative and qualitative accordingly. The findings showed that the application of this fusion learning methods has stimulated a better understanding of particular topics in economics. In addition, it showed an increasing trend related to students’ achievement during cycles. Lastly, the use of combination learning models could be implemented by considering relevant issues in the classroom.Keywords: Problem Based Learning, Think Pair Share, Learning Result